An Analysis of Swearing Words Used by Characters in Blood Father Movie - Rahmadi, Dwi, Agus Wijayanto, Ph.D, Mauly Halwat Hikmat, Ph.D (2017)
This study aims at identifying the types of swearing words used by all characters in Blood Father Movie and the factors contributing those swearing. It is a descriptive qualitative research which formulates the conclusion by collecting, classifying, and interpreting the data. The data is elicited through documentation technique then classified based on theory before interpreted. The source of the data is the script of the movie taken from the internet. The utterances containing swearing words are used as the data of the research. The types of swearing words which found in this research are 5 stand-alone functions, 4 slot filler functions, and 4 themes. The stand-alone functions include expletive interjection (58 data or 27%), oaths (2 data or 1%), curses (4 data or 2%), unfriendly suggestion (4 data or 2%), name-calling (55 or 25%). The slot fillers are adjectival intensifier (4 data or 2%), adjective of dislike (6 data or 4%), emphasis (72 data or 34%), and modal adverbial (6 data or 3%). The themes are religious theme (24 data or 11%), scatological theme (40 data or 20%), sex organ theme (2 data or 1%), and sexual activities theme (147 data or 68%). Among the three factors which contribute to swearing, the most dominant factor is neurological (80 data or 38%). After that is psychological factor (73 data or 34%) and the least dominant factor is sociocultural (60 data or 24%). Keywords: swearing words, Blood Father movie, types of swearing, factors contributing swearing